Parto domiciliar planejado acompanhado por enfermeira : a experiência da mulher, da família e do profissional - Frank, Tatianne Cavalcanti (2011)
A woman with low-risk pregnancy can have as environment to give birth her own home. The World Health Organization recognizes the home as a suitable and safe place for the birth, due to the good obstetric outcomes and for facilitate the rescue of the birth physiology, since it is the woman's choice and that she and her family receive a safe care in the moment of the birth, with guarantee of quality of care with reference systems. The home birth is still rising in the country and it is an irreversible trend. Thus, it is essential to know the particularities that permeate it in order to contribute in building of foundations for this practice. So, this study aimed to understand the experience of planned home birth by the actors involved in the birth process. It is a descriptive research, with qualitative approach. It was approved by the Standing Committee on Ethics in Research Involving Humans (COPEP) of State University of Maringá / PR, under the approval number 544/2010 and developed in the municipality of Cascavel/PR. The data collection occurred between April and May 2011, through an episodic recorded interview using a semi-structured form. 34 people participated of the study, 08 of these were women, 18 family members and 08 professionals who had the experience of giving birth or following the birth process at home in a planned way. For data analysis it was used content analysis proposed by Minayo (2008). The results were showed in three articles. In Article 1, which sought to understand the women's perception, there was indication that the home allowed their protagonism and of their family by the peace and calm that the environment provides and for being of them domain. The women noticed the home care by the nurses as something that favors the autonomy, which contributed to a successful and physiological evolution of birth, lower painful perception, absence of unnecessary interventions, respect to the contact and the link between mother-child at birth, better physical recovery at postpartum and higher adaptation to maternity. Still, the successful outcome of births generated in women the desire to repeat the experience in future pregnancies, as well as they recommended this type of birth for other women. The Article 2 revealed that the partner and family members were invited and encouraged to be part of the whole process. They felt them as fundamental in the physical and emotional support to woman and as contributors for a good evolution of birth. In Article 3, the environment was considered safe to follow requirements for the treatment as low-risk pregnancy, suitable assessment during the birth, presence of suitable materials, transdisciplinary network and predefined local for referrals. It was concluded that home is a space of care that provides to the woman and to the family autonomy and protagonism at birth process. It is a safe strategy and an option to transform and improve the quality of obstetric care, contributing to the reduction of iatrogenesis and unnecessary interventions and consequently contributes to the reduction of maternal and perinatal mortality.